Pengaruh Pendekatan Problem Solving Terhadap Kemampuan Menyelesaikan Soal Cerita Materi Teorema Phytagoras - Nunung Setiawati; Abdul Rahman; Vernita Sari (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2024)
This study aims to find out that the use of problems solving approach has a positive effect on students' abilities in solving story problems on the Pythagorean theorem class VIII.5 UPTD SMP Negeri 18 Barru. This type of research is quasi-experimental without a control class conducted in one group. The variables studied in this study were students' ability to solve word problems on the Pythagorean theorem class VIII.5 UPTD SMP Negeri 18 Barru as the dependent variable and learning using the problems solving method as the independent variable. The population of this study were all students of class VIII UPTD SMP Negeri 18 Barru for the academic year 2022/2023 which consisted of 5 (five) classes. Sampling was carried out by cluster random sampling, from 5 classes one class was taken randomly namely class VIII.5 as the experimental class. The instruments used in this study were tests of the ability to solve the Pythagorean theorem word problems and validated student activity observation sheets. Based on the descriptive statistical analysis, the average score of students' ability to solve the Pythagorean theorem story problems before learning using the problem solving learning method was 63,37 and the average score of students' ability to solve the Pythagorean theorem story problems after learning using the problem solving method was 80,40. Based on inferential statistical analysis using the one sample t-test, a significant value was obtained, p = 0,004 < a = 0, this means that H0 is rejected H1 is accepted. So it can be concluded that there is a positive effect of the problem solving learning method on the mathematics learning outcomes of class VIII.5 UPTD SMP Negeri 18 Barru.